Pengaruh Financing To Deposit Ratio (FDR) Terhadap Return On Asset (ROA) Dengan Variabel Intervening Penempatan Dana Pada Sertifikat Bank Indonesia Syariah (SBIS) Pada Bank Syariah di Indonesia - Mawardi, Imron (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to investigate the effect of Financing to Deposit Ratio (FDR) toward investment in Islamic Certificate of Bank Indonesia (SBIS), effect of investment in Islamic Certificate of Bank Indonesia (SBIS) toward Return on Asset (ROA), and effect of Financing to Deposit Ratio (FDR) toward Return on Asset (ROA) Islamic Bank in Indonesia.Methodology that used in this study is a quantitative approach. Technique analysis that used in this study is path analysis. Samples are used in this study collected from Islamic Bank Statistic Data issued by Bank Indonesia, January 2009 until October 2013, the total amount were 58 data.The results show that Financing to Deposit Ratio (FDR) has significantly negative effect on Islamic Certificate of Bank Indonesia (SBIS). Islamic Certificate of Bank Indonesia (SBIS) has not significantly effect on Return on Asset (ROA). Financing to Deposit Ratio (FDR) has significantly positive effect on Return on Asset (ROA). Financing to Deposit Ratio (FDR) with Islamic Certificate of Bank Indonesia (SBIS) as intervening variable have negative effect on Return on Asset (ROA) Islamic Bank in Indonesia.